2016
DOI: 10.1007/s11999-015-4317-7
|View full text |Cite
|
Sign up to set email alerts
|

Does Residency Selection Criteria Predict Performance in Orthopaedic Surgery Residency?

Abstract: Background More than 1000 candidates applied for orthopaedic residency positions in 2014, and the competition is intense; approximately one-third of the candidates failed to secure a position in the match. However, the criteria used in the selection process often are subjective and studies have differed in terms of which criteria predict either objective measures or subjective ratings of resident performance by faculty. Questions/purposes Do preresidency selection factors serve as predictors of success in resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
88
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 31 publications
11
88
2
Order By: Relevance
“…Thus, it seems that for specialties that prioritize an individual clerkship grade when evaluating applicants, such as orthopedic surgery does with the surgery clerkship, using an individual grade may not be a reliable criterion. Prior studies 5,10 have reported correlations between medical school grades (ie, number of honors grades) and objective outcome measures of orthopedic resident success, including OITE scores and ABOS Part I scores. However, our study demonstrates that there is a wide variation in the distribution of honors grades among all clerkships, with an average 30% of students receiving an honors grade for each clerkship across all medical schools analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems that for specialties that prioritize an individual clerkship grade when evaluating applicants, such as orthopedic surgery does with the surgery clerkship, using an individual grade may not be a reliable criterion. Prior studies 5,10 have reported correlations between medical school grades (ie, number of honors grades) and objective outcome measures of orthopedic resident success, including OITE scores and ABOS Part I scores. However, our study demonstrates that there is a wide variation in the distribution of honors grades among all clerkships, with an average 30% of students receiving an honors grade for each clerkship across all medical schools analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Our data add to the growing body of literature suggesting that USMLE Step 2 CK may be a better predictor of resident performance. 22,24,[31][32][33][34] Reasons for these findings may be secondary to USMLE Step 2 CK being more clinically relevant or closer in time to residency graduation and board examinations. Reasons for why having an advanced degree was associated with higher patient communication scores may include residents having more life experience, more maturity, and/or completion of a previous rigorous training program.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence for USMLE Step 2 CK, USMLE Step 1 scores continue to be one of the highest cited factors used by many residency programs in selecting applicants for interviews, although the available evidence suggests residency programs may do better by giving more weight to USMLE Step 2 CK in the application process. 22,24,[31][32][33][34] A major limitation of our study was that it was completed at a single institution and all clinical performance was measured only from a unique IM residency ambulatory long block structure. In addition, the staff, peer, and allied health assessment tools used in our program did not have significant supportive validity evidence for use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 3 is taken during the first year of residency and evaluates the application of medical knowledge to the supervised practice of medicine. Of these, Step 1 scores have been shown to play an important role in residency selection by standardizing academic achievements of students from different schools, in predicting success in clinical clerkships and Step 2 examinations, and in board examinations taken during residencies [3][4][5][6][7][8][9]. Therefore, parameters influencing student performance on Step 1 examinations such as the Medical College Admission Test (MCAT) and related preparatory materials are of interest to both students as well as medical schools.…”
Section: Introductionmentioning
confidence: 99%